From Recognition to Investment: Sustaining the Monibi Indigenous Community - Waha, Caecilia Johanna Julietta; Kumar Jha, Gautam (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
The safeguarding of Economic, Social, and Cultural Rights (ESCR) for Indonesia's indigenous populations is essential but precarious, as exemplified by the Monibi people. Although recognized nationally as Intangible Cultural Heritage since 2016, the Monibi possess no regional legal status, resulting in a regulatory void. In the absence of prompt legal action, this extended uncertainty jeopardizes the physical and cultural existence of the community. This engenders significant tensions where customary territories intersect with National Park areas, limiting traditional access to vital resources. This research utilizes a socio-legal methodology to investigate the conflict between statutory conservation mandates and the socioeconomic conditions of the Monibi. The report advocates for a paradigm change towards a sustainable investment model as the principal means of rights enforcement. The findings indicate that a customized investment framework is critically required to address the impasse between governmental entities and traditional land users. This research presents an innovative legislative framework that employs equitable investment strategies to harmonize conservation objectives with the safeguarding of indigenous ESCR.